Sand production simulation under true-triaxial stress conditions - Younessi Sinaki, Ahmad Reza (Curtin University, 2012)
Sand production in weakly consolidated sandstone reservoirs could result in damaging the production and surface facilities. Sanding includes two stages: the failure of sandstone around the borehole and sand grains being transported into the borehole. The first stage is related to stresses around the borehole whereas the second one is controlled by drawdown pressure. In order to avoid sanding, the stresses around the borehole and the drawdown pressure which initiate sanding are studied.This research simulated sand production through laboratory experiments and numerical simulations. The effect of three independent far-field stresses was investigated which is contrary to most of the current studies being performed under a uniaxial or triaxial stress state. Accordingly, a unique experimental setup and procedure was introduced to conduct sand production experiments under true-triaxial stress conditions. The effect of drawdown pressure and state of far-field stresses on the sanding mechanism and development of the failure zone around a borehole were investigated. The experiments were conducted on 100×100×100 mm3 cubic samples of synthetic sandstones. The samples were manufactured using an established procedure developed to produce samples with properties similar to weakly consolidated sandstone. The properties of the synthetic sandstone samples were determined by conducting a series of standard rock mechanics tests on cylindrical plugs. Using a true-triaxial stress cell (TTSC), cubic samples were subjected to three independent boundary stresses and uniform lateral fluid flow from the outer boundaries. The fluid flows through the sample radially and discharges from a hole drilled at the centre of the sample: this allows the study of sanding initiation by changing the state of stress, sample material and fluid properties.In this research, firstly, the concept of sand production from a geomechanics point of view and a summary of previous sanding experiments are explained. Thereafter, the procedure to prepare a sample suitable for sand production experiments is provided. Subsequently, the experimental equipment, setup and procedure are explained in detail. This is followed by presenting the results of two sets of experiments performed at different states of stress. The effect of changing the lateral stresses on the development of the failure zone around borehole was investigated in these experiments. During these experiments it was observed that a minimum drawdown pressure is needed to initiate sand production, regardless of the state of the boundary stresses. In addition, it was observed that the geometry (i.e. width and depth) of the failure zone developed around the borehole is a function of the state of stresses.The experiments were also simulated numerically using ABAQUS in order to gain a better understanding of sand production mechanisms. The numerical modelling procedure and results are presented in a separate section in this thesis. Good agreement was obtained between the results of both experimental and numerical methods which confirm the importance of the state of stresses on the evolution of sanding. Based on the experimental and numerical observations, it was shown that the effect of the magnitude of the maximum lateral stress on the depth of failure is more significant than the minimum lateral stress.